2022
DOI: 10.7759/cureus.21641
|View full text |Cite
|
Sign up to set email alerts
|

The Unexpected Formation of a Broncho-Esophageal Fistula of the Right Main Stem Bronchus Status Post Esophageal Stent Placement: A Case Report

Abstract: This case presents a patient with a history of non-small cell lung carcinoma who had radiation therapy complicated by esophageal dysphagia. She had a fully covered self-expanding metal stent (SEMS) placed one year ago in the proximal region of her esophagus prior to this admission. She presented to the emergency department (ED) for dyspnea on exertion. Imaging showed a persistent right lower lobe opacity, and bronchoscopy revealed a right broncho-esophageal fistula (BEF). Further investigation by endoscopy fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As reported by Patel et. al., in the case of a patient with non-small cell lung carcinoma, the fully covered SEMS placed to improve esophageal dysphagia migrated distally and led to the formation of a BEF [33]. In this case, the fully covered stent was replaced with a partially covered one, while a gastrostomy/jejunostomy tube was placed to facilitate feeding [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by Patel et. al., in the case of a patient with non-small cell lung carcinoma, the fully covered SEMS placed to improve esophageal dysphagia migrated distally and led to the formation of a BEF [33]. In this case, the fully covered stent was replaced with a partially covered one, while a gastrostomy/jejunostomy tube was placed to facilitate feeding [33].…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al reported the formation of BEF as a delayed complication of a fully covered SEMS insertion. The patient, diagnosed with non-small cell lung carcinoma, had a SEMS placed in the proximal region of her esophagus to alleviate the esophageal dysphagia that occurred as a result of radiation therapy [33]. After 1 year post insertion, the fully covered SEMS migrated distally and caused the formation of her BEF; the fully covered SEMS was replaced with a partially covered SEMS that led to the resolution of the fistulous tract [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation